Gender and Climate Smart Agriculture: Co-creating a Learning Agenda - Puskur, Ranjitha; Mishra, Avni (CGIAR GENDER Impact Platform, 2022)
What is a Learning Agenda? A set of questions, planned activities and products that facilitate learning and decision making within an organization or project/programme around a specific theme. A coordination tool for identifying knowledge gaps and answers a range of priority questions within a given budget and timeframes.